ANALISIS PERUBAHAN TUTUPAN LAHAN DI NAGARI KOTO SANI TAHUN 2002 – 2022 (CONTOH ANALISIS KASUS DALAM PEMBELAJARAN GEOGRAFI) - Amor Setiawan; Nofrion Nofrion (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
The purpose of this research is to help educators to be able to teach remote sensing material in the classroom, by taking examples from raw Landsat images that are processed simply using spatial applications. And this teaching material is based on a case study of using imagery as a land cover analysis in Koto Sani village. Then this study resulted that the material used as teaching material was valid and the practical use of this teaching material was practical enough so that it could be used as remote sensing teaching material.